2016
DOI: 10.1097/qai.0000000000000847
|View full text |Cite
|
Sign up to set email alerts
|

Reassuring Birth Outcomes With Tenofovir/Emtricitabine/Efavirenz Used for Prevention of Mother-to-Child Transmission of HIV in Botswana

Abstract: Background Prior to introduction of tenofovir/emtricitabine/efavirenz (TDF/FTC/EFV), 3-drug antiretroviral treatment (ART) was associated with increased adverse birth outcomes when used for prevention of mother-to-child HIV transmission (PMTCT) in Botswana. Methods We extracted obstetric records from all women at the 2 largest maternities in Botswana from 2009-11 when Botswana National Guidelines recommended ZDV from 28 weeks gestational age (GA) for CD4 ≥350 and ART for CD4 <350, and again in 2013-14 after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
82
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(97 citation statements)
references
References 32 publications
13
82
2
Order By: Relevance
“…However, the Botswana data are reassuring in that the combination of tenofovir, emtricitabine, and efavirenz was not associated with higher rates of adverse pregnancy outcomes than zidovudine-based ART. 12 In conclusion, the PROMISE trial showed superior efficacy of triple-drug ART, as compared with zidovudine plus single-dose nevirapine, for the prevention of mother-to-child transmission in HIV-infected women with high CD4 cell counts but also showed higher rates of adverse events. On the basis of recent trials, the WHO recommends ART for HIV-infected persons regardless of CD4 cell count, and there are clear benefits of ART for the prevention of mother-to-child transmission and maternal health.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…However, the Botswana data are reassuring in that the combination of tenofovir, emtricitabine, and efavirenz was not associated with higher rates of adverse pregnancy outcomes than zidovudine-based ART. 12 In conclusion, the PROMISE trial showed superior efficacy of triple-drug ART, as compared with zidovudine plus single-dose nevirapine, for the prevention of mother-to-child transmission in HIV-infected women with high CD4 cell counts but also showed higher rates of adverse events. On the basis of recent trials, the WHO recommends ART for HIV-infected persons regardless of CD4 cell count, and there are clear benefits of ART for the prevention of mother-to-child transmission and maternal health.…”
Section: Discussionmentioning
confidence: 88%
“…A study in Botswana that compared birth outcomes in women receiving tenofovir-based ART (with efavirenz) or zidovudine-based ART (primarily with nevirapine) showed no significant differences in preterm delivery or stillbirth. 12 A potential biologic cause may be a pharmacokinetic interaction between lopinavir-ritonavir and tenofovir; decreased renal clearance of tenofovir and increased plasma and intracellular levels, particularly in women, have been reported with concomitant administration. [13][14][15] In the PROMISE trial, the lopinavir-ritonavir dose was increased during the third trimester because pharmacokinetic studies showed decreased lopinavir-ritonavir levels with standard doses in late pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Prematurity was reported in ten studies. 9,10,16,21,[23][24][25][26][27][28] ART initiation before conception was associated with signifi cantly higher risk of prematurity than ART initiation after conception (pooled RR 1·20, 95% CI 1·01-1·44; fi gure 2). Between-study heterogeneity was signifi cant (I²=77%, 95% CI 57·3-87·4; p=0·0001), suggesting that about three-quarters of the variability in the measures of the association is due to heterogeneity between studies rather than chance (fi gure 2).…”
Section: Resultsmentioning
confidence: 99%
“…After review of the title and abstract, 187 full-text articles were selected for reading, and 11 studies met inclusion criteria (fi gure 1). 9,10,16,[21][22][23][24][25][26][27][28] The studies included participants recruited during the period 1986-2012 (table 1). Three were done in the UK, 10,23,26 two in Botswana, 9,28 and one each in Brazil, 24 France, 27 South Africa, 25 and Tanzania; 16 the remaining two studies 21,22 included participants from the European Collaborative Study (ECS).…”
Section: Resultsmentioning
confidence: 99%
“…6 Thus in high HIV prevalence settings it is essential to understand how ART use may influence the risk of preterm delivery. Findings on the association between ART use and adverse birth outcomes, including PTD, are conflicting 7,8 and possibly associated with ART regimen used, timing of initiation and ART eligibility criteria.…”
Section: Introductionmentioning
confidence: 99%